A TRIPARTITE EVOLUTIONARY GAME INVOLVING QUALITY REGULATION OF PREFABRICATED BUILDING PROJECTS CONSIDERING GOVERNMENT REWARDS AND PENALTIES - Wang, Heping; Zhang, Zhenke; Li, Yan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
In recent years, there have been great efforts to develop prefabricated buildings and to promote the EPC mode. However, various types of construction quality accidents have frequently occurred, and the emergency management agency reported 272 prefabricated construction accidents in China between 2018 and 2022. To improve the quality regulation of prefabricated buildings, this paper constructs a tripartite evolutionary game model of the government, EPC general contractors, and supervision units. It analyzes the stability of the evolutionary strategies of all parties involved, and it tests the influence of the reward and punishment mechanism, rent-seeking costs, and other factors on the choice of tripartite strategies through simulation. The results show the following: When government regulators increase the punishment and set reasonable reward quotas, EPC general contractors choose to standardize construction, and supervision units supervise strictly. EPC general contractors and supervision units evolve in a positive direction if the sum of rewards and punishments is higher than the gains from speculation. Government regulation evolves to be stricter if higher authorities increase the punishment for lack of regulation.